Analisa Kemampuan Berpikir Kreativitas Anak Usia Dini dengan Teori Graham Wall - Matius Timan Herdi Ginting (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
Children's creativity, defined as the ability to think originally and flexibly, is evident in drawing, playing, and various creations. Observations at Permata Ibu Kindergarten show that students have low curiosity, get bored quickly, are passive, and have limited imagination, which indicates a potential lack of creative thinking skills. This study aims to describe the creative thinking abilities of early childhood children at Permata Ibu Kindergarten. The research was conducted in 2023 using a qualitative descriptive approach, referring to the stages of Graham Wallas' creative thinking process. The research location is Permata Ibu Kindergarten in Palangka Raya, with 5 large group students as subjects. Data collection techniques include observation, unstructured interviews, and tests (writing numbers, reading, writing words/letters, and counting). Data were analyzed using data reduction, data presentation, and conclusion drawing, and their validity was tested thru source triangulation and technique triangulation. The research results show that during the preparation stage, students are able to recognize the types of questions and recall relevant information. During the incubation stage, some students exhibited brief thinking behavior before attempting to solve the problem. During the illumination stage, most students were able to generate ideas or solution steps, although some still struggled to explain their thinking process. During the verification stage, not all students rechecked their answers or generated alternative solutions. Out of the five students, three were at the creative thinking level category 2 (moderately creative), one was category 1 (less creative), and one was category 0 (not creative). These findings indicate variations in creative thinking abilities among early childhood children and the need for learning strategies that are more stimulating to creativity